Neonatal Sepsis and Associated Factors Among Newborns in Woldia and Dessie Comprehensive Specialized Hospitals, North-East Ethiopia, 2021 - Birrie E; Sisay E; Tibebu NS; Tefera BD; Zeleke M; Tefera Z (Infection and Drug Resistance, 2022)
Endalk Birrie,1 Ermias Sisay,2 Nigusie Selomon Tibebu,2 Birhanu Desu Tefera,1 Mulusew Zeleke,1 Zenebe Tefera1 1School of Nursing and Midwifery, College of Medicine and Health Sciences, Wollo University, Wollo, Ethiopia; 2Department of Pediatrics and Child Health Nursing, College of Health Science, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Endalk Birrie, School of Nursing and Midwifery, College of Medicine and Health Sciences, Wollo University, PO Box 1145, Wollo, Ethiopia, Tel +251 928543030, Email eeab2008@gmail.comIntroduction: Neonatal sepsis is a clinical illness characterized by infection-related signs and symptoms in the first month of life, with or without bacteremia. Septicemia, meningitis, pneumonia, arthritis, osteomyelitis, and urinary tract infections are all examples of systemic illnesses that can affect newborns. Hence, the main aim of this study was to assess the prevalence and factors associated with neonatal sepsis among newborns in Woldia and Dessie Comprehensive Specialized Hospitals, northeast Ethiopia, from January 1 to July 30, 2021.Methods: This institution-based cross-sectional study was conducted from January 1 to July 30, 2021, on 344 randomly selected neonates who visited the hospital. A systematic random sampling technique was used to select samples, and data were collected using a pre-tested standardized questionnaire. For data entry and analysis, Epi Data version 4.1 and SPSS version 24 applications were used, respectively. The goodness-of-fit was tested by the Hosmer–Lemeshow statistic test. Bivariable and multivariable binary logistic regressions were used to identify associated factors at a 95% confidence interval. Significance was considered at p-value < 0.05.Results: In this study, the prevalence of neonatal sepsis was 79.4% (95% CI: 75.2– 83.6%). Maternal UTI/STI history [AOR: 3.1; 95% CI (1.5– 7.1)], gestational age < 37 weeks [AOR: 4.4; 95% CI (1.0– 8.9)], PROM [AOR: 4.9; 95% CI (2.5– 6.8)], and new-born resuscitation history [AOR: 2.3; 95% CI (1.5– 4.3)] were all significantly associated with neonatal sepsis.Conclusion: This study indicates that the proportion of neonatal sepsis is high. A history of maternal PROM, being a preterm neonate, a history of maternal UTI/STIs, and having received resuscitation at birth were identified as risk factors for neonatal sepsis.Keywords: neonatal sepsis, neonatal infection, neonatal intensive care unit, hospitals, north east, Ethiopia